Hubungan Kadar Serum 25 (OH) Vitamin D Ibu Hamil Trimester III Dengan Luaran Maternal - Rasud, Rismawati; Aminuddin, Aminuddin; AM, Nasrudin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective:This study aims to determine the relationship the relationship of serum levels of 25 (OH) vitamin D third trimester pregnant women with maternal outcomes,method: The study design was observational cohort design with a number of samples are 62 third trimester pregnant women were taken by purposive sampling at 32-37 weeks gestation The RSIA SitiKhadijah 1 Makassar In November-December 2019. The relationship was tested by using Chi-square.results: The results of analysis by using chi-squre showed higher levels of serum (OH) D does not have a significant relationship to the incidence of hypertension (0401) infection (0145) in the third trimester pregnant women.Conclusion: Levels of 25 (OH) D is not always a factor causing the incidence of hypertension and infection in pregnancy.KEYWORDS:Serum 25 vitamin D, trimester III pregnant women, maternal output